CULTURALLY RESPONSIVE PEDAGOGY AND STUDENTS ENGAGEMENT IN TEACHER TRAINING COLLENGES WITHIN THE BAMENDA MUNICIPALITY (American Journal of Pedagogical and Educational Research, 2026)
Engagement in Teacher Training Colleges in Bamenda Municipality. Specifically, the study sought to investigate the extent to which culturally responsive pedagogical practices influence student engagement within teacher training institutions. To achieve this purpose, two specific research objectives were formulated and corresponding hypotheses were established to guide the investigation.The study adopted a concurrent nested mixed-method research design, integrating both quantitative and qualitative research paradigms to provide a comprehensive understanding of the phenomenon under investigation. From the target population, a sample of 200 student teachers and teacher educators from teacher training colleges was selected through the simple random sampling technique, constituting the accessible population of the study. Data were collected using two principal research instruments: a structured four-point Likert-scale questionnaire for the collection of quantitative data and a semi-structured interview guide designed to elicit qualitative data from teacher educators.Data analysis was carried out using a methodological triangulation approach to enhance the validity and robustness of the findings. Quantitative data were analyzed using both descriptive and inferential statistical techniques, whereas qualitative data were subjected to thematic content analysis. Inferential analysis was performed using regression analysis to test the formulated hypotheses at a 0.05 level of significance. The reliability of the research instruments was established using the Cronbach Alpha reliability coefficient, with values ranging from 0.70 to 0.844, demonstrating satisfactory levels of internal consistency and instrument reliability.